2006
DOI: 10.1038/sj.onc.1209799
|View full text |Cite
|
Sign up to set email alerts
|

Reg I-knockout mice reveal its role in regulation of cell growth that is required in generation and maintenance of the villous structure of small intestine

Abstract: Reg I (regenerating gene product I) is a growth factor that plays a central role in the generation and regeneration of the gastric mucosal architecture. On the other hand, mouse Reg I mRNA is expressed at the highest levels in the small intestine among the gastrointestinal tissues. In the current study, with the aim to clarify the role of Reg I protein in the small intestine, the temporal and spatial pattern of Reg I expression and the phenotype of Reg I-knockout mice in the tissue were examined. In the wild-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 31 publications
2
36
1
Order By: Relevance
“…Conversely, along with others, we have suggested that REG family proteins are importantly involved in the regeneration of gastrointestinal mucosa by exerting mitogenic and/or antiapoptotic effects. 4,6,27,41 Accordingly, together with our present data, it is tempting to speculate that REG family proteins are pivotal targets for IL-22 in protecting the colonic mucosa from inflammation-associated injury, although further studies will be needed to test this hypothesis.…”
Section: Discussionmentioning
confidence: 92%
“…Conversely, along with others, we have suggested that REG family proteins are importantly involved in the regeneration of gastrointestinal mucosa by exerting mitogenic and/or antiapoptotic effects. 4,6,27,41 Accordingly, together with our present data, it is tempting to speculate that REG family proteins are pivotal targets for IL-22 in protecting the colonic mucosa from inflammation-associated injury, although further studies will be needed to test this hypothesis.…”
Section: Discussionmentioning
confidence: 92%
“…Regenerating islet (Reg) proteins have been identifi ed in various types of regenerating tissues [10,11,51,52] and cancer cells [ 13,14,16 ] and the expression patterns of Reg genes have been under intense scrutiny. To date, however, there clearly demonstrate an increase in Reg1 expression in mouse MIN6 insulinoma β-cells treated with gastrin.…”
Section: Discussionmentioning
confidence: 99%
“…The Reg2 protein is a potent mitogen of Schwann cells and contributes to the regeneration of motor neurons in mice [ 10 ]. Moreover, the generation and maintenance of the villous structure of the small intestine is infl uenced by Reg1, which is considered a regulator of intestinal cell growth [ 11 ]. Despite the intimate link between Reg proteins and the proliferation and/or differentiation of diverse types of cells, no information is available, to date, about the expression and regulation of members of the Reg family in embryonic stem cells (ESCs).…”
mentioning
confidence: 99%
“…9 The following primary antibodies were used in this study: monoclonal mouse IgG2a anti-mouse proliferating cell nuclear antigen (Santa Cruz Biotechnology) (1:1000) and monoclonal mouse IgG2a anti-rat RegI antibody (1:50). 11 For double staining of Tg RegI protein and chromogranin A, the tissue slides were first stained for RegI as described above.…”
Section: Histopathological Analysismentioning
confidence: 99%
“…8 Previous reports 9,10 showed that the mouse stomach, in contrast to the rat stomach, shows very low levels of RegI expression, providing an ideal experimental system with which to test the effects of the regI transgene. Tg mice of 3 weeks old, just finishing the period of gastric gland morphogenesis, showed apparent gastric mucosal hypertrophy and elevated expression of a cell proliferation marker, compared with littermate controls.…”
mentioning
confidence: 99%